On the Janowski Starlikeness of the Coulomb Wave Functions. (31st March 2022) - Noreen, Saddaf; Raza, Mohsan; Deniz, Erhan; Malik, Sarfraz Nawaz
Abstract : In this article, we are interested in finding sufficient conditions on A, B, L, and η which ensure the normalized Coulomb wave function to be Janowski starlike. Sufficient conditions are also obtained for g L, η / z ∈ P A, B, which readily yield conditions for g L, η to be close-to-convex.